Professional training in physiotherapy: barriers to the diversification of practical learning scenarios and for teaching-service integration - Ana Paula Maihack Gauer; Fátima Ferretti; Carla Rosane Paz Arruda Teo (Editora Champagnat, 2018)
Abstract Introduction: Professional training in health, at present, aims to develop competencies and skills for a performance according the principles of the Unified Health System (SUS, in Portuguese). In this sense, the Ministries of Health and Education have set up devices for training reorientation that prioritize teaching-service integration and diversification of learning scenarios. Objective: To describe barriers to the diversification of practical learning scenarios and for teaching-service integration in a physiotherapy course from the perspective of teachers and students. Methods: This is a qualitative research developed according to the case study method, with the participation of 16 students and 11 teachers-physiotherapists. During the data collection three focus groups were established, two with students and one with professors, besides individual interviews with both the course coordinator and the pedagogical articulator of the National Program for the Reorientation of Professional Health Training of the assessed course. Data were analyzed through thematic content analysis. Results: Among the identified barriers there are students' low participation in public health services; saturation of public health services for students to carry out practical activities; low number of physiotherapists in Primary Care; indirect relationship of Clinical School with SUS. Conclusion: In order to improve the teaching-service interaction and to diversify the learning scenarios it is necessary to prioritize an integrated planning of actions to overcome identified barriers, including the participation of both the university managers and health services.